Is low birth weight associated with lower adiponectin levels? - A systematic review and meta-analysis - Afnan Sabah Alhakeem; Aleyna Hasturk; Trine Witzner Hessel Lawaetz; Tue Helms Andersen; Charlotte Brøns; Allan Arthur Vaag (PLoS ONE, 2025)
Individuals born with low birth weight are at increased risk of type 2 diabetes, which potentially may be attributed to immature adipose tissue development and reduced levels of the insulin-sensitizing adipokine, adiponectin. This systematic review and meta-analysis synthesize data from 67 studies, comprising over 8000 individuals across various age groups, to examine the relationship between circulating adiponectin levels and birth weight. The results revealed that individuals with low birth weight have significantly lower adiponectin levels compared to those born with normal birth weight (SMD = −0.46 μg/ml [95% CI: −0.57; −0.35], P < 0.0001). Moderate heterogeneity was observed (I 2 = 67%, P < 0.01), but sensitivity analysis and meta-regression did not identify specific factors driving this variation. Pooled Pearson correlation analysis indicated a moderate but statistically significant positive correlation between birth weight and adiponectin levels (correlation estimate = 0.31 [95% CI: 0.16; 0.46], P < 0.0001). These findings suggest that reduced adiponectin levels in low birth weight individuals may contribute to their elevated risk of type 2 diabetes, potentially offering new insights into the developmental origin of this disease.